An 'antifouling' porous loofah sponge with internal microchannels as solar absorbers and water pumpers for thermal desalination. Issue 25 (18th June 2020) - Liu, Chao; Hong, Kevin; Sun, Xiao; Natan, Avi; Luan, Pengcheng; Yang, Yang; Zhu, Hongli
Abstract : We found that a type of fruiting body, the loofah, can enable efficient solar-driven steam generation based on the integrated bilayers and microchannels. Under illumination of one Sun, the steam generation rate and efficiency achieved 1.42 kg m −2 h −1 and 89.9%, respectively. Abstract : As a new solar technology, interface steam generation has great prospects in the application of desalination and fractionation. Herein, we report a sustainable, efficient, and accessible loofah-based solar evaporator with a bilayer structure. The top carbonized layer functioned as efficient solar absorbers with broad light absorption and high light trapping. At the bottom layer, attributed to loofah fibers' natural hydrophilicity and hierarchical macropores and microchannels, sufficient water was pumped to the localized heating interface. During desalination, the salt concentration gradient between the macropores and microchannels allowed for efficient salt drainage in the loofah and prevented the accumulation of salt on the surface of the evaporator, thus ensuring long-term stability. This economical light absorber and the water-pumping natural fibers exhibited a steam generation rate of ∼1.42 kg m −2 h −1 and an efficiency of 89.9% under one Sun. This low cost, abundant, and stable material is promising for future large-scale solar steam applications.